2007
DOI: 10.1152/physiolgenomics.00026.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fgl2deficiency causes neonatal death and cardiac dysfunction during embryonic and postnatal development in mice

Abstract: We hypothesized that cardiac dysfunction was responsible for the high perinatal lethality that we previously reported in fibrinogen-like protein 2 (Fgl2) knockout (KO) mice. We therefore used ultrasound biomicroscopy to assess left ventricular (LV) cardiac structure and function during development in Fgl2 KO and wild-type (WT) mice. The only deaths observed between embryonic day (E)8.5 (onset of heart beating) and postnatal day (P)28 (weaning) were within 3 days after birth, when 33% of Fgl2 KO pups died. Hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 55 publications
0
33
1
Order By: Relevance
“…The direct prothrombinase activity of fgl2 is implicated in the pathogenesis of several inflammatory disorders including fulminant hepatitis and severe hepatitis, alloand xeno-graft rejection [4,11,12] . Furthermore, its role is also evidenced in murine and human cytokine induced fetal loss [5,[13][14][15] and neonatal death from contractile dysfunction and rhythm abnormalities during embryonic and postnatal development [16] . The observations that neutralizing Abs to mfgl2 prevent both fibrin deposition and death from MHV-3 infection support its role as a coagulant [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The direct prothrombinase activity of fgl2 is implicated in the pathogenesis of several inflammatory disorders including fulminant hepatitis and severe hepatitis, alloand xeno-graft rejection [4,11,12] . Furthermore, its role is also evidenced in murine and human cytokine induced fetal loss [5,[13][14][15] and neonatal death from contractile dysfunction and rhythm abnormalities during embryonic and postnatal development [16] . The observations that neutralizing Abs to mfgl2 prevent both fibrin deposition and death from MHV-3 infection support its role as a coagulant [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of in vivo evidences indicate that fgl2 serves as a multifunctional protein [11], [55]. In addition, it has been reported that fgl2 may be a more important procoagulant than tissue factor in xenograft acute vascular rejection characterized by fibrin deposition in situ or microvascular thrombosis [11], [56].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-ultrasound has proved valuable for in vivo phenotyping of defects in cardiovascular function in embryos and during postnatal development caused by genetic alterations. Examples include evaluations of cardiac function in embryos with mutations in Fgl2, NFATc1, BMPRIA or Baf60c [50,[59][60][61]. Important cardiovascular events occur at birth when the placenta is lost from the circulation and a large increase in pulmonary blood flow occurs.…”
Section: Evaluation Of Embryonic and Postnatal Cardiovascular Developmentioning
confidence: 99%
“…Further developmental changes in cardiac function occur in the weeks following birth and these can be monitored by micro-ultrasound (e.g. [50,53,54]). A growing area of research in developmental biology investigates how the early environment of the embryo and neonate influences long-term cardiovascular outcomes in adulthood (e.g.…”
Section: Evaluation Of Embryonic and Postnatal Cardiovascular Developmentioning
confidence: 99%